The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1063/1.446724
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational behavior of molecular constituents of organic superconductors: TMTSF, its radical cation and the sulphur analogs TMTTF and TMTTF+

Abstract: The results of an extensive vibrational analysis of tetramethyltetrathiafulvalene (TMTTF) and tetramethyltetraselenafulvalene (TMTSF) and of their radical cations are presented. The polarized infrared absorption spectra of oriented crystalline samples of neutral TMTTF and TMTSF (4000–80 cm−1) are reported and compared with powder and solution spectra. The polarization data are used as a basis for the symmetry assignment of the infrared active fundamental modes. Powder and solution Raman spectra are presented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
1
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 52 publications
6
62
1
1
Order By: Relevance
“…They found that the intermolecular a g (ν 3 ) mode, which becomes infra-red active through electron-molecular-vibration coupling, splits below T CO . This feature is explained by the strong dependence of this vibronic mode with the degree of ionization of the TMTTF molecule 66 . From this study, it is estimated a charge disproportionation ratio of 5 : 4 and 2 : 1 for X = PF 6 and AsF 6 salts, respectively.…”
Section: B the Symmetry Breaking Co Transitionmentioning
confidence: 94%
“…They found that the intermolecular a g (ν 3 ) mode, which becomes infra-red active through electron-molecular-vibration coupling, splits below T CO . This feature is explained by the strong dependence of this vibronic mode with the degree of ionization of the TMTTF molecule 66 . From this study, it is estimated a charge disproportionation ratio of 5 : 4 and 2 : 1 for X = PF 6 and AsF 6 salts, respectively.…”
Section: B the Symmetry Breaking Co Transitionmentioning
confidence: 94%
“…In the present paper, we relate our assignments of the vibrational modes to the nomenclature proposed by Meneghetti and coworkers [59] where the molecular structure of TMTTF is assumed to have D 2h symmetry. According to the character table for the D 2h point group (Table 2), there are eight different irreducible representations whereas only the antisymmetric b 1u , b 2u and b 3u modes are infrared active and the symmetric a g , b 1g , b 2g , b 3g are Raman active.…”
Section: Tmttf Molecule and Vibrational Modesmentioning
confidence: 99%
“…Sketch of the totally symmetric a g modes ν 3 and ν 4 and the asymmetric ν 28 (b 1u ) stretching modes of the TMTTF molecule that mainly involve the central and outer C=C bonds. In the right frame, we show the linear shift of the intramolecular vibrations ν 3 (a g ) and ν 28 (b 1u ) with the charge per TMTTF molecule obtained from optical spectroscopy by Meneghetti et al [59]. …”
Section: Introductionmentioning
confidence: 99%
“…We suggest that both modes originate from the ν 51 (b 2u ) in-plane vibration of the TMTSF molecule. According to the normal-coordinate analysis [12,16] its frequency for a free TMTSF 0.5+ cation is 702 cm −1 . The corresponding atomic movements involve stretching of the Se-C side bond and rocking of the adjacent methyl group.…”
Section: Vibrational Modesmentioning
confidence: 99%
“…The TMTSF molecule with the point group symmetry D 2h has in total 72 local vibrational modes classified according to the following representations [12] …”
Section: Vibrational Modesmentioning
confidence: 99%